Deuterium Isotope Separation using LiCl–KCl–LiH–LiD Molten Salt - Toranosuke Nago; Yutaro Norikawa; Kenji Harada; Mikito Ueda; Hisayoshi Matsushima; Toshiyuki Nohira (ECS Advances)
The separation of hydrogen isotopes is an important process in materials science, medicine, and nuclear energy. In this study, we attempted hydrogen isotope separation via electrolysis and H–D exchange reaction using LiCl–KCl–LiH–LiD molten salt at 673 K. In the molten-salt system, H and D exist as H ^− and D ^− , respectively, unlike that in the conventional aqueous solution. The diffusion coefficient of D ^− was determined by cyclic voltammetry in LiCl–KCl–LiD molten salt. Furthermore, H was enriched in the exhaust gas via both electrolysis and the H–D exchange reaction in molten LiCl–KCl containing equal quantities of LiH and LiD. D _2 gas and H ^− are exchanged on a Pt-black catalyst in the molten salt.